2019
DOI: 10.1139/apnm-2018-0454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning age on the small intestine mucosa of rats

Abstract: Weaning of mammalian progeny is associated with a change in food composition and mother–offspring separation. Weaning results in a critical period of low voluntary feed intake, during which the animal is adapting to the starter diet. To evaluate the effects of weaning age on morphological changes that occur in the intestines of rats, we assessed intestinal histomorphometry and somatic growth in 21-days-old pups and 90-days-old mature rats that had been weaned early (day 16), normally (day 21), or late (day 26)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Consistent with previously reported results, weaning stress resulted in severe damage to the colon, which morphologically manifested as high crypt density loss, hyperplasia, and compromised mucosal integrity ( 36 , 37 ). The intestine of weaning piglets is not fully functionally developed and cannot adapt to sudden dietary transitions and/or environmental changes, which may be the main cause of weaning-associated intestinal inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previously reported results, weaning stress resulted in severe damage to the colon, which morphologically manifested as high crypt density loss, hyperplasia, and compromised mucosal integrity ( 36 , 37 ). The intestine of weaning piglets is not fully functionally developed and cannot adapt to sudden dietary transitions and/or environmental changes, which may be the main cause of weaning-associated intestinal inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that short infancy (early weaning) is associated with characteristic fast reproduction long body, underweight, glucose tolerance and insulin sensitivity, but also in large testes and large liter [7]. Among the smallest mammals, testes size is associated with high copulatory frequency and sperm production [15], as observed also in the rats of the present study.…”
Section: Blood Vessel-stroma Ratiosupporting
confidence: 84%
“…To evaluate the long-term consequences of early and late weaning and the effect on testicular size, testicular size was determined daily from day 30 once a week until day 90 using a self-built orchidometer based on the human Prader orchidometer with mock-ups ranging from 0.5 to 5ml [7].…”
Section: Short-term Effectsmentioning
confidence: 99%
“…We have previously shown that in humans a delayed infancy-childhood transition has a lifelong impact on stature [1][2] and that correspondingly in the rat, the age at weaning from lactation determines a rat's growth trajectory, but also body composition and maturational tempo [3]. We showed that early-weaned rats developed faster than normal than late weaned rats; as day 30 and until adulthood early weaned were leaner and longer than late-weaned animals, which were heavier and shorter [3][4]. Early-weaned progeny mature more rapidly, females showed earlier vaginal opening and estrous and males showed earlier onset of testicular growth [3,5].…”
Section: Introductionmentioning
confidence: 61%